Indolyl imine compounds as multi-target agents; synthesis, antidiabetic, anticholinesterase, antioxidant activities and molecular modeling - Ceyhan, Sadik M.; Zengin, Irem Nur; Bingul, Murat; Sahin, Hasan; Boga, Mehmet; Saglam, Mehmet F.; Kandemir, Hakan (Elsevier, 2024)
A new range of indolyl imine system 3d-l has been successfully prepared from 4,6-dimethoxy-2,3-diphenylindole-7-carbaldehyde 2a and 4,6-dimethoxy-3-aryl-indole-7-carbaldehyde 2b-c via Schiff base reaction. The structure of targeted compounds was confirmed by 1H and 13C NMR, FT-IR, mass spectrometry and single crystal X-ray diffraction techniques. The indolyl imine derivatives were also subjected to in vitro antidiabetic activities employing alpha-glucosidase and alpha-amylase enzymes. In terms of antidiabetic investigation, the alpha-glucosidase enzyme was found to be potential target due to the comparable inhibition concentrations with the standard acarbose and the compound 3e exhibited better potency than the standard. The anticholinesterase potency of the compounds was investigated towards the acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) enzymes. The compounds displayed moderate efficiency against the BChE enzyme with the best inhibition concentration of 30.48 mu M by the compound 3h. The antioxidant properties of final compounds were determined by DPPH radical scavenging, ABTS Cation Radical Decolarization and CUPRAC Cupric Reducing Antioxidant Capacity assay methods. The ABTS cation scavenging assay provided the best responses for the compounds and the candidates 3k and 3l were determined as promising targets for the antioxidant activity. Plausible binding mode and interaction of ligands with the selected enzyme have been studied by molecular docking, supporting the experimental results. In silico ADME showed high drug likeness of the synthesized compounds.
Keywords: Indole; alpha-Amylase; alpha-Glucosidase; Anticholinesterase; Antioxidant; Molecular Modeling